ESTIMATION OF GROWTH, MORTALITY, AND EXPLOITATION STATUS OF NURSE TETRA (Brycinus nurse) AND TRUE BIG SCALE TETRA (Brycinus macrolepidotus) (FAMILY: ALESTIDAE) FROM THE NEW CALABAR RIVER, NIGERIA - Olaniyi Alaba Olopade; Henry Eyina Dienye; Uzoma C Nworgu (Research Center for Fisheries, 2019)
This study aimed to determine the growth patterns, mortality, and exploitation status of two species of Alestidae in the New Calabar River, Nigeria. For this purpose, fish samples were collected monthly from three landing sites from the local fishermen using gill nets (mesh sizes: 15-25mm), beach seine (mesh sizes: 2.3-10mm), and cast nets (mesh sizes: 15 -25mm). The length-weight relationship revealed exponent “b” value for Brycinus nurse was 3.54 and 3.21 for Brycinus macrolepidotus while the condition factors were 1.08 and 1.02 for Brycinus nurse and Brycinus macrolepidotus respectively. The growth parameters of Brycinus nurse asymptotic length (L) and growth coefficient (K) were 24.46 cm and 0.52 yr-1, respectively, while those for Brycinus macrolepidotus L was 28.88 cm and K was 0.22 yr-1. The reproductive load (L50/L) ratio was found to be 0.59 and 0.61 for B. nurse and B. macrolepidotus, respectively. Exploitation rate (E) for B. nurse was 0.26 and 0.11 for B. macrolepidotus while length-at-first capture (Lc) was 14.49 cm for B. nurse and 17.64 cm for B. macrolepidotus. The natural mortality was greater than the fishing mortality for both species and Logistic regression of the probability of capture routine values recorded for B. nurse were higher than that of B. macrolepidotus. Maximum exploitation rate (Emax) was less than 0.5 for both B. nurse (0.41) and B. macrolepidotus (0.42). These values were close to the maximum allowable limit; therefore, the species may be unsustainable when fishery intensifies in the future. To ensure sustainable exploitation of the two Alestid species in the area, fishing effort should be regulated.